2020
DOI: 10.1088/1742-6596/1473/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Gifford-McMahon Cryocoolers

Abstract: Cryocoolers are devices which produce the required refrigeration at a specific low temperature, and they can replace the normal cryogenic fluids. Cryogenic fluids give refrigeration only at a specific temperature whereas cryocooler can produce refrigeration at varying low temperatures. There are many types of cryocoolers like Pulse tube, Stirling, Joule-Thomson, Gifford-McMahon (GM) etc. Many advances have occurred over the years in these cryocoolers. For obtaining very low temperatures along with large coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Finally, it is observed that the amount of gas that remains in the hot chamber A (after the exhaust valve is closed), which recirculates in the next cycle and which mixes with the gas coming from the compressor, is always negligible. In fact, it represents about 0.8% of the total gas that completes the cycle (see Table 1) Through this analysis Theoretically and experimentally, we have found some conclusions that are congruent with other experimental works [15][16][17][18]: indeed, the regenerator is the most critical part of the machine.…”
Section: Exergy Cycle Analysissupporting
confidence: 86%
“…Finally, it is observed that the amount of gas that remains in the hot chamber A (after the exhaust valve is closed), which recirculates in the next cycle and which mixes with the gas coming from the compressor, is always negligible. In fact, it represents about 0.8% of the total gas that completes the cycle (see Table 1) Through this analysis Theoretically and experimentally, we have found some conclusions that are congruent with other experimental works [15][16][17][18]: indeed, the regenerator is the most critical part of the machine.…”
Section: Exergy Cycle Analysissupporting
confidence: 86%